Income effects of poverty alleviation relocation program on rural farmers in China - Gan-xiao LENG; Xiao-long FENG; Huan-guang QIU (Journal of Integrative Agriculture, 2021)
This paper analyses the impact of the poverty alleviation relocation (PAR) program on rural household income and evaluates the heterogeneous income effects of various relocation modes, based on a panel dataset of relocated households from 16 counties in eight Chinese provinces. The results show that participation in the PAR increases the income of both rural and urban resettlers. More specifically, it has a significant positive effect on agricultural and wage income for rural and urban resettlers, respectively. Further analyses show that the income increase for rural resettlers was mainly due to agricultural technology training and that the income increase for town resettlers was attributed to medical security. For the village resettlers, policies should focus on strengthening the development of local industries and training of agricultural technologies. For the urban resettlers, non-agricultural employment and public services in the urban resettlement areas should be promoted.